Education, neurosis and exception: What really matters in education during/beyond the pandemic?. Issue 2 (1st June 2021) - Menezes, Pedro; Menezes, Isabel; Ribeiro, Norberto
This study examines newspaper articles about education published in a reference daily newspaper in Portugal during the measure taken to close schools as a way of containing the COVID-19 epidemic. During this three-month period, a total of 105 news items were collected involving several educational and political actors: government representatives from the areas of education, health and work, parents, teachers, school principals, union representatives and, on rare occasions, even students. A qualitative analysis of these news items based on thematic analysis revealed themes that appear at the core of schools ‐ i.e. that are essential and should be resumed as soon as possible. Amid the 'state of exception', 'neurotic citizenship' is reinforced and managed by the government. Within this context, participation and inclusion seem to disappear from the discourse of education and are captured by work and economic issues that go beyond education itself.